Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the equation [tex]\(x^2 + 4 = 0\)[/tex], we will follow a systematic approach:
1. Rewrite the equation:
[tex]\[ x^2 + 4 = 0 \][/tex]
2. Isolate the [tex]\(x^2\)[/tex] term:
[tex]\[ x^2 = -4 \][/tex]
3. Recognize that we need to take the square root of both sides.
4. Take the square root of both sides:
[tex]\[ x = \pm \sqrt{-4} \][/tex]
5. Simplify the square root of [tex]\(-4\)[/tex]:
[tex]\[ \sqrt{-4} = \sqrt{4 \cdot (-1)} = \sqrt{4} \cdot \sqrt{-1} \][/tex]
Knowing that [tex]\(\sqrt{4} = 2\)[/tex] and [tex]\(\sqrt{-1} = i\)[/tex]:
[tex]\[ \sqrt{-4} = 2i \][/tex]
Thus, the solutions to the equation [tex]\(x^2 + 4 = 0\)[/tex] are:
[tex]\[ x = \pm 2i \][/tex]
So, the correct answer is:
[tex]\[ x = \pm 2i \][/tex]
1. Rewrite the equation:
[tex]\[ x^2 + 4 = 0 \][/tex]
2. Isolate the [tex]\(x^2\)[/tex] term:
[tex]\[ x^2 = -4 \][/tex]
3. Recognize that we need to take the square root of both sides.
4. Take the square root of both sides:
[tex]\[ x = \pm \sqrt{-4} \][/tex]
5. Simplify the square root of [tex]\(-4\)[/tex]:
[tex]\[ \sqrt{-4} = \sqrt{4 \cdot (-1)} = \sqrt{4} \cdot \sqrt{-1} \][/tex]
Knowing that [tex]\(\sqrt{4} = 2\)[/tex] and [tex]\(\sqrt{-1} = i\)[/tex]:
[tex]\[ \sqrt{-4} = 2i \][/tex]
Thus, the solutions to the equation [tex]\(x^2 + 4 = 0\)[/tex] are:
[tex]\[ x = \pm 2i \][/tex]
So, the correct answer is:
[tex]\[ x = \pm 2i \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.